2009
DOI: 10.1007/s11695-009-9959-7
|View full text |Cite
|
Sign up to set email alerts
|

Voice Feature Characteristic in Morbid Obese Population

Abstract: The voices of individuals with morbid obesity are different of the voice of nonobese people and demonstrate significant changes in vocal characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 2 publications
4
42
2
2
Order By: Relevance
“…Therefore, it is useful for the voice clinician to understand these interdependencies. Specific factors that may be potentially related to voice production/physiology are body weight and body fat volume (1)(2)(3)(4) . However, the voice literature regarding the impact of body weight on selected parameters of vocal physiology and phonation is sparse.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is useful for the voice clinician to understand these interdependencies. Specific factors that may be potentially related to voice production/physiology are body weight and body fat volume (1)(2)(3)(4) . However, the voice literature regarding the impact of body weight on selected parameters of vocal physiology and phonation is sparse.…”
Section: Introductionmentioning
confidence: 99%
“…Of course, a larger number of studies on these aspects is required, as these results may be due to pneumo-phono-articulatory incoordination, which is common in children 7 , or may even be found to be occasional, since there is no support in the literature with other works that have specifically researched the MPT/ė/ MPT/e/ in the population of the same age group. Moreover, the comparison with other links , probably due to reduced subglottic airway pressure 8 .…”
Section: Discussionmentioning
confidence: 93%
“…Obese patients' voices were characterized as hoarse (62%), breathy (27%) and with instability to phonation (44%). The authors attributed these characteristics to low MPT values found in obese patients, that would cause irregular vibration of the vocal folds due to reduced subglottic pressure, resulting in a hoarse and breathy voice 8 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations